Comparing the Efficacy of Ligasure System vs Conventional Electrocautery for Modified Radical Mastectomy in Breast Cancer Patients - Azeem, Sanwal; Shaheen, Uzma; Anwar, Muhammad; Akhtar, Naveed; Rasheed, Uzma; Ullaha, Shafiq (Biological and Clinical Sciences Research Journal, 2025)
Modified radical mastectomy (MRM) is a standard surgical approach for breast cancer management. Conventional electrocautery and advanced vessel-sealing devices such as LigaSure Small Jaw are commonly used for dissection and hemostasis. However, their comparative efficacy regarding operative time, blood loss, and surgical outcomes remains an area of interest. Objective: To compare the efficacy of conventional electrocautery and LigaSure Small Jaw in breast cancer patients undergoing modified radical mastectomy. Methodology: A prospective study was conducted in the Oncology and Surgery Department of Nishtar Hospital from December 2023 to December 2024. A total of 100 female breast cancer patients with ASA scores 1 and 2 undergoing modified radical mastectomy were included in the study. The patients were divided into an electrocautery group, including 50, and the LigaSure SmallJaw group, including 50. The mastectomy was performed under general anesthesia. Axillary clearance was performed by either a monopolar diathermy probe or LigaSure SmallJaw. Results: Intraoperative outcomes significantly improved in the LigaSure group compared to the electrocautery group. The operative time was 120.9 ± 15.2 minutes in the electrocautery group and 110.2 ± 20.7 minutes in the LigaSure group (p=0.005). The blood loss was 189 ± 20.6ml and 118.3 ± 60.81 ml, respectively (p=0.002). Conclusion: Compared to conventional electrocautery, the LigaSure SmallJaw system has better efficacy and operative outcomes, including shorter surgery duration and intraoperative blood loss.